Prevalence of Multidrug-Resistant CTX-M Extended Spectrum Beta-Lactamase-Producing Escherichia coli From Different Bovine Faeces in China - Wei, Xiaojuan; Wang, Weiwei; Lu, Ningning; Wu, Lingyu; Dong, Zhen; Li, Bing; Zhou, Xuzheng; Cheng, Fusheng; Zhou, Kairen; Cheng, Haijian; Shi, Hongmei; Zhang, Jiyu (Frontiers in Veterinary Science, 2022)
CTX-M extended spectrum beta-lactamase-producing Escherichia coli cause severe health hazards in livestock breeding. To date, little is known about antibiotic resistance differences among bacterial isolates from yaks, cows, and beef cattle; therefore, the aims of this study were to analyse the prevalence of CTX-M-producing E. coli in yak, beef cattle, and dairy cattle feces from different provinces in China. A total of 790 fecal samples from yaks, beef cattle, and dairy cows were used. Among all the samples, 523 non duplicate E. coli isolates were identified, and 29.6% of samples harbored CTX-M producers. The results showed that these E. coli strains harbored 15 clusters of CTX-M genes: CTX-M-79, CTX-M-55, CTX-M-15, CTX-M-14, CTX-M-28, CTX-M-179, CTX-M-65, CTX-M-24, CTX-M-27, CTX-M-102, CTX-M-105, CTX-M-173, CTX-M-238, CTX-M-196, and CTX-M-10. The dominant resistance genes were CTX-M-15, CTX-M-14, and CTX-M-55. Moreover, the distribution of CTX-M genes was related to geographical region. Based on the above findings, we reasoned that bovines are potential reservoirs of antibiotic resistance, and this problem should be given adequate attention.